2017
DOI: 10.2147/bctt.s123785
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of host polymorphisms in genes that clinically characterize breast cancer tumors and pretreatment cognitive performance in breast cancer survivors

Abstract: PurposeInspired by the hypothesis that heterogeneity in the biology of breast cancers at the cellular level may account for cognitive dysfunction symptom variability in survivors, the current study explored relationships between host single-nucleotide polymorphisms (SNPs) in 25 breast cancer-related candidate genes (AURKA, BAG1, BCL2, BIRC5, CCNB1, CD68, CENPA, CMC2, CTSL2, DIAPH3, ERBB2, ESR1, GRB7, GSTM1, MELK, MKI67, MMP11, MYBL2, NDC80, ORC6, PGR, RACGAP1, RFC4, RRM2, and SCUBE2), identified from clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Six focused on breast cancer (BC) patients [19][20][21][22][23][24], one reported on both BC and lymphoma patients [25], and three reported on other patient groups [26][27][28]. The remaining seven studies reported results from studies investigating other genes than APOE, e.g., COMT [24,29] and BDNF [14,24], with five of these studies focusing on BC patients [14,[29][30][31][32], one on prostate cancer patients [33], and one on patients with mixed non-CNS cancers [34]. See Table 2 for overview of genotypes and patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six focused on breast cancer (BC) patients [19][20][21][22][23][24], one reported on both BC and lymphoma patients [25], and three reported on other patient groups [26][27][28]. The remaining seven studies reported results from studies investigating other genes than APOE, e.g., COMT [24,29] and BDNF [14,24], with five of these studies focusing on BC patients [14,[29][30][31][32], one on prostate cancer patients [33], and one on patients with mixed non-CNS cancers [34]. See Table 2 for overview of genotypes and patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Using the NIH Quality Assessment Tool [18], each study received a quality rating (range: 0-14). Eight studies [14,19,20,23,[25][26][27]33] were rated 'good quality' (>9 criteria met), and the remaining nine studies [21,22,24,[28][29][30][31][32]34] were rated 'fair quality' (5-9 criteria met). Study quality ratings are shown in Supplementary Table S3.…”
Section: Study Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of ORC3 has not yet been documented in tumors. However, a single nucleotide polymorphism of ORC6 was reported as a breast cancer-related candidate gene [66]. Xi et al found that ORC6 was highly expressed in tumors compared to paired normal tissues in colorectal cancer [67].…”
Section: Discussionmentioning
confidence: 99%